A peptide of 17 aminoacids from the N-terminal region of maize plastidial transglutaminase is essential for chloroplast targeting - Campos, Nefertiti; Villalobos, Enrique; Fontanet, Pilar; Torné, Josep M.; Santos, Mireya (Scientific Research Publishing, 2012)
Transglutaminases (TGases, EC 2.3.2.13) catalyse posttranslational modification of proteins by establishing ε-(γ-glutamyl) links and covalent conjugation of polyamines. In plants, the functionality of these enzymes is scarcely known. The maize transglutaminase gene (tgz), the only cloned plant TGase, produces major alterations in thylakoid membrane architecture when the transglutaminase (chlTGZ) protein was over-expressed in tobacco chloroplasts, significantly increasing the number of grana stacked layers. Here we demonstrate that nuclear transformation of rice plants starting from a tgz gene truncated in 17 N-terminal aas (tgzt) non altered chloroplast thylakoid structures. F3 transformed plants were analysed for TGase activity, chlTGZ presence and tgzt transcription levels. Transformed plants exhibited double the in vitro TGase activity of the non-transformed plants. Immunoblot and quantitative RT-PCR analysis results of tgzt-rice plants grown under different illumination periods revealed that chlTGZ maintains its differential expression depending on the light regime. Nevertheless, the maize protein was localised by confocal microscopy in the cell wall of transformed rice cells. TEM analyses of the transformed cells showed normal, non-altered chloroplast thylakoid structures with the maize protein preferentially located in the cell walls. The results confirmed that the tgz eliminated sequence is essential for chloroplast targeting, being its absence sufficient to the lack of protein expression in its original plastidal compartment. Interestingly, the immunolocalization of a putative endogenous rice TGase protein is also showed. These data give further information on plant TGase functionality and its relationship to photosynthetic membranes.
Keywords: Chloroplast Transit Peptide; Localization; Maize Transglutaminase; Nuclear Transformation; Oryza Sativa; Zea Mays